Identification of essential anthropometric and health-related markers for effective weight loss program in middle-aged women - Nurul Hidayah Mat; Rabiu Muazu Musa; Fanora Mat; Zaffira Firzana Zaffri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Effective weight loss programs should consider more than just total body weight reduction, incorporating other critical anthropometric and health-related markers.